A T cell redirection platform for co-targeting dual antigens on solid tumors - Leonie Enderle; Karim H. Shalaby; Maryna Gorelik; Alexander Weiss; Levi L. Blazer; Marcin Paduch; Lia Cardarelli; Anthony Kossiakoff; Jarrett J. Adams; Sachdev S. Sidhu (Taylor & Francis Group, 2021)
In order to direct T cells to specific features of solid cancer cells, we engineered a bispecific antibody format, named Dual Antigen T cell Engager (DATE), by fusing a single-chain variable fragment targeting CD3 to a tumor-targeting antigen-binding fragment. In this format, multiple novel paratopes against different tumor antigens were able to recruit T-cell cytotoxicity to tumor cells in vitro and in an in vivo pancreatic ductal adenocarcinoma xenograft model. Since unique surface antigens in solid tumors are limited, in order to enhance selectivity, we further engineered "double-DATEs" targeting two tumor antigens simultaneously. The double-DATE contains an additional autonomous variable heavy-chain domain, which binds a second tumor antigen without itself eliciting a cytotoxic response. This novel modality provides a strategy to enhance the selectivity of immune redirection through binary targeting of native tumor antigens. The modularity and use of a common, stable human framework for all components enables a pipeline approach to rapidly develop a broad repertoire of tailored DATEs and double-DATEs with favorable biophysical properties and high potencies and selectivities.